Phosphoproteomics analysis of hypopharyngeal glands of the newly emerged honey bees (Apis mellifera ligustica) - Saboor Ahmad; Khalid Ali Khan; Hamed A. Ghramh; Jianke Li (Journal of King Saud University: Science, 2022)
The most important honey bee queen food royal jelly is produced by the exocrine hypopharyngeal glands (HGs) of the worker honey bees. The HGs exhibits diverse gene and protein that create age-related physiological adaptations. However, limited knowledge is available on how the phosphorylation process is responsible for physiological alterations across the development of HGs in newly emerged bees. This study measured the acinus of HGs and characterized its phosphoproteomics analysis between the newly emerged bees of royal jelly bees (RJBs) and Italian bees (ITBs). Phosphopeptides of HGs were enriched by Ti4+-IMAC reagents, followed by protein identification via Q-Exactive LC-MS/MS. Our findings indicated that the mean acinus size of HGs of newly emerged bees of RJBs was significantly larger (56.18 ± 1.72 µm) than ITBs (45.98 ± 1.62 µm). A total of 1576 phosphopeptides with 1800 phosphosites containing 525 phosphoproteins were identified in RJBs, while 746 phosphopeptides, of which 846 phosphosites correspond to 317 phosphoproteins were identified in ITBs. Most proteins were phosphorylated on 1 residue followed by 2 and 3 residues in newly emerged bees of both bee stocks. In addition, serine phosphorylation was most observed, followed by threonine and tyrosine in both bee stocks. In newly emerged bees of RJBs, the protein metabolic process, glycolytic process, and formation of translation preinitiation were uniquely enriched, while protein translation, peptide metabolic process and elongation were enriched in ITBs. This research shows detailed phosphorylation of HGs and provides helpful information for understanding the biological activities of HGs development in newly emerged bees from both bee stocks.